Voluntary intake, digestibility and nitrogen utilization by sheep fed ensiled grass clover mixture harvested at three stages of maturity - Marina Vranić; Mladen Knežević; Krešimir Bošnjak; Goran Perčulija; Hrvoje Kutnjak (Mljekarstvo)
The objective of this experiment was to study the effects of grass maturity at harvest on silage ad libitum intake, in vivo digestibility and N retention in wether sheep. The sward was harvested at the stem elongation, tasseling and flowering growth stages of orchardgrass (Dactylis glomerata). Three silages were offered to four Charolais wether sheep in an incomplete change over design with four periods. As the crop matured, there was an increase (P<0.001) in dry matter (DM), organic matter (OM) and acid detergent fiber (ADF) concentration and a decrease in crude protein (CP) concentration (P<0.001). Increasing maturity of grass ensiled showed a linear decrease (P<0.01) in voluntary silage intake of DM, OM, neutral detergent fiber (NDF), a linear decrease (P<0.01) in digestibility of silage DM, OM, NDF, ADF, CP, and a linear decrease in nitrogen balance (P<0.01). No quadratic response was recorded in silage intake, digestibility or N balance. The results suggest that grass maturity at harvest influences the nutritive value of grass silage, in terms of ad libitum intake, in vivo digestibility and N retention in sheep, as a result of changes in chemical composition.